STUDI KOMPARASI KONSEP PENDIDIKAN ANAK DALAM ISLAM: PERSPEKTIF IBNU QAYYIM AL-JAUZIYYAH DAN NASHIR BIN SULAIMAN AL-UMAR - Wafa’ Az-Zahro; Mega Satria Nurul Falah (LPPM IAD Probolinggo, 2025)
This study aims to explore and analyze the concept of children’s education as presented by two scholars: Nashir bin Sulaiman al-Umar and Ibnu Qayyim al-Jauziyyah. It also seeks to identify the similarities and differences between their perspectives on educating children. The research applies a qualitative method using a library research approach, with data drawn primarily from the original works of both scholars. The findings show that Ibnu Qayyim al-Jauziyyah, in Tuhfat al-Mawlūd bi Ahkām al-Mawlūd, emphasizes children’s education through the values of faith, morality, adherence to Sharia, work ethic, and intellect. His suggested methods include habituation, role modeling, advice, encouragement, and constructive discipline. In contrast, Nashir bin Sulaiman al-Umar, in Buyūt Muṭma’innah, highlights values such as monotheism, morality, compassion, empathy, respect for parents, and intellect, with methods including dialogue, role modeling, habituation, attention, gentleness, and prayer. Both scholars share a similar foundation of values and methods, but differ in approach. Ibnu Qayyim presents a more systematic framework grounded in Islamic jurisprudence, supported by references to the Qur’an, Sunnah, and classical scholars. Meanwhile, Nashir’s approach is more empathetic, marked by an emphasis on gentleness toward children, the use of language that appeals to the heart, and contemporary examples relevant to parents’ lives. Keywords: Children’s Education; Educational Values; Educational Methods; Nashir Bin Sulaiman Al-Umar; Ibn Qayyim Al-Jawziyyah